KOMUNIKASI THERAPEUTIC COMMUNITY PASIEN PENYALAHGUNA NARKOBA DIMASA PANDEMI COVID-19 - Laila Zakiyatu Zahro; Rama wijaya Kesuma Wardani; Pasiska Pasiska (INSTITUT AGAMA ISLAM NEGERI METRO, 2021)
This study will examine the Therapeutic Community Communication of Drug Abuse Patients during the Covid-19 Pandemic